2016
DOI: 10.1099/jmm.0.000258
|View full text |Cite
|
Sign up to set email alerts
|

Comparative functional properties of engineered cationic antimicrobial peptides consisting exclusively of tryptophan and either lysine or arginine

Abstract: We previously reported a series of de novo engineered cationic antibiotic peptides (eCAPs) consisting exclusively of arginine and tryptophan (WR) that display potent activity against diverse multidrug-resistant (MDR) bacterial strains. In this study, we sought to examine the influence of arginine compared to lysine on antibacterial properties by direct comparison of the WR peptides (8-18 residues) with a parallel series of engineered peptides containing only lysine and tryptophan. WR and WK series were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 66 publications
4
42
0
Order By: Relevance
“…Particularly, it can be used to get information on the kinetics of binding. Different studies have used SPR to study interactions of membrane active peptides with model membranes [ 237 , 238 , 239 , 240 ].…”
Section: Live Imagingmentioning
confidence: 99%
“…Particularly, it can be used to get information on the kinetics of binding. Different studies have used SPR to study interactions of membrane active peptides with model membranes [ 237 , 238 , 239 , 240 ].…”
Section: Live Imagingmentioning
confidence: 99%
“…The positively charged residues (Arg and Lys) have been shown to be extremely important for the activity of the peptides, due to their ability to promote electrostatic attraction with the negatively charged membrane of microorganisms such as bacteria [ 9 , 10 ]. Similarly, bulky hydrophobic residues, including Trp, have been shown to play a key role for most AMPs in the hydrophobic interactions that occur subsequent to the initial electrostatic attraction [ 11 , 12 ]. However, the same residues that are essential for the activity of AMPs also constitute an Achilles’ heel when they are considered for systemic use against infections.…”
Section: Introductionmentioning
confidence: 99%
“…A study of the antimicrobial peptide amide BP100, KKLFKKILKYL, showed that a single substitution with arginine at lys 9 improved antimicrobial activity without any detectable increase in toxicity [24]. Another study of antimicrobial peptides consisting of exclusively arginine and tryptophan of varying length showed that arginine compared to lysine could yield some antimicrobial peptides with enhanced antimicrobial activity [27]. However, improvements in the antimicrobial activity was not seen for 33-36.…”
Section: Manipulating Cationicity By Lys-arg Substitutions (Compound mentioning
confidence: 99%